Peran Granulasi dan Pengayaan Terhadap Peningkatan Efektivitas Kompos pada Sawi, Selada, Kangkung, dan Bayam - Yudi Sastro, I krarwati, Suwandi (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2012)
ABSTRACTThis study aimed at determining the effect of granulation and compost enrichment to improve the effectivity of compost on green mustard, lettuce, kangkong, and spinach. The granulation treatments i.e without and with granulation and the enrichment using microbial cultures, the liquids from the rock phosphate fermentation, and the mixture of microbial cultures and the liquids from the rock phosphate fermentation were as treatments . The combinations of treatments were arranged using completely randomized block design with 20 replications. Variables observed were plant height, leaf number, fresh weight and dry weight. The data were analyzed using analysis of variance and foll owed by Duncan's Multiple Range Test. The results showed that there was no significant interaction between granulation with enrichment to improve the effectivity of compost on green mustard, lettuce, kangkong, spinach. The compost granulation treatment significantly increased the effectivity of compost on green mustard and lettuce, but not on kangkong and spinach. The granulation even decreased the compost effectiveness on spinach. The compost enrichments treatments significantly increased the effectivity of compost on green mustard, lettuce and spinach. The compost enrichments using the mixture of liquid fermentation medium of rock phosphate and microbial increased yield of green mustard and lettuce up to 48.4 and 60.1% respectively, while liquid fermentation medium of rock phosphate increased yield of spinach 75.0%.Key words: compost, granulation, enrichment, vegetableABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh granulasi dan pengayaan terhadap efektivitas kompos pada sawi, selada, kangkung, dan bayam. Perlakuan penelitian terdiri atas perlakuan granulasi, yakni tanpa dan dengan granulasi, dan perlakuan pengayaan yang meliputi kultur mikroba, cairan media fermentasi batuan fosfat, dan campuran kultur mikroba dan cairan media fermentasi batuan fosfat. Kombinasi perlakuan diatur menggunakan Rancangan Acak Kelompok Lengkap dengan pengulangan sebanyak 20 kali. Peubah pengamatan meliputi tinggi tanaman, jumlah daun, dan berat segar serta berat kering tanaman. Data hasil pengamatan dianalisis menggunakan analisis varian dan dilanjutkan menggunakan Duncan Multiple Range Test. Hasil penelitian menunjukkan bahwa tidak terdapat interaksi nyata antara perlakuan granulasi dan pengayaan terhadap peningkatan efektivitas kompos pada sawi, selada, kangkung dan bayam. Perlakuan granulasi nyata meningkatkan efektivitas kompos pada sawi dan selada, namun tidak pada kangkung dan bayam. Perlakuan granulasi bahkan menurunkan efektivitas kompos pada bayam. Pengayaan nyata meningkatkan efektivitas kompos pada sawi, selada, dan bayam. Pengayaan kompos menggunakan campuran kultur mikroba dan cairan medium fermentasi batuan fosfat meningkatkan hasil sawi dan selada, masing-masing hingga 48,4 dan 60,1%, sedangkan cairan medium fermentasi batuan fosfat meningkatkan hasil bayam sebesar 75%.Kata kunci: kompos, granulasi, pengayaan, sayuran